2003
DOI: 10.1002/chem.200305337
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium‐Mediated Cross‐Coupling of Terminal Alkynes and Vinyl Bromides: Selective Synthesis of Cyclobutene and 1,3‐Diene Derivatives

Abstract: A diastereoselective synthesis of 1,3-butadiene or cyclobutene derivatives by a zirconium-mediated reaction of alkenyllithium compounds and vinyl bromides is reported. The key steps involve the generation of zirconocene-alkyne complexes from haloalkenes and subsequent coupling with alkenyl bromides. Thus, formally the process supposes the cross-coupling reaction between a terminal alkyne and an alkenyl bromide. Moreover, the use of butyl vinyl ether instead of vinyl bromide as the unsaturated system allows an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…These initial studies were followed by a deeper investigation into the reaction of alkynezirconocene complexes and alkenyl bromides. [34] These studies demonstrated a more complex process than that described in Scheme 21. Thus, it was shown that the reaction of alkynezirconocene complexes 108, which are obtained by the reaction of alkenyllithium compounds 107 and zirconocene methyl chloride, with alkenyl bromides 109 gives dienes 110 and/or 111 depending on the structure of both the starting alkenyllithium derivative 107 and the alkenyl bromide 109 (Scheme 22).…”
Section: Alkynezirconocene Complexes Reaction With Heterosubstitutedmentioning
confidence: 95%
See 1 more Smart Citation
“…These initial studies were followed by a deeper investigation into the reaction of alkynezirconocene complexes and alkenyl bromides. [34] These studies demonstrated a more complex process than that described in Scheme 21. Thus, it was shown that the reaction of alkynezirconocene complexes 108, which are obtained by the reaction of alkenyllithium compounds 107 and zirconocene methyl chloride, with alkenyl bromides 109 gives dienes 110 and/or 111 depending on the structure of both the starting alkenyllithium derivative 107 and the alkenyl bromide 109 (Scheme 22).…”
Section: Alkynezirconocene Complexes Reaction With Heterosubstitutedmentioning
confidence: 95%
“…Experimental support for this mechanism was found by the isolation, under appropriate reaction conditions, of several cyclobutenes derived from complex 114. [34] Takahashi and co-workers have also been involved in the study of the reaction of alkynezirconocene complexes and heterosubstituted alkenes (enol ethers and alkenyl halides). [35] This work differs from that developed by Barluenga and co-workers described above in the method used for the generation of the alkynezirconocene complex.…”
Section: Alkynezirconocene Complexes Reaction With Heterosubstitutedmentioning
confidence: 99%
“…It should be noted that the outcome of the intramolecular reaction of an alkene−zirconocene complex and a six-membered cyclic enol ether is different from the intermolecular version of the reaction; see ref b.…”
Section: Referencesmentioning
confidence: 99%
“…Transition-metal-mediated strategies that form new C−C bonds are outstanding methods in the construction of these medium-sized rings . During the last years, we have been involved in the study of the reaction of organozirconium complexes and enol ethers. , In this context, we are especially interested in the development of new zirconium-catalyzed C−C bond forming reactions . On the basis of our findings in this field, it was tempting to design a zirconium-based approach directed toward those attractive synthetic targets.…”
mentioning
confidence: 99%
“…In particular, we are interested in the reactivity of enol ethers and alkenyl halides . In this context, we found that cyclobutene derivatives could be obtained, under particular conditions, by the reaction of alkyne−zirconocene complexes and alkenyl bromides …”
mentioning
confidence: 99%